Biosynthetic Polymalic Acid as a Delivery Nanoplatform for Translational Cancer Medicine. Issue 3 (March 2021) - Zhang, Jianguo; Chen, Deyu; Liang, Guoxin; Xu, Wenrong; Tao, Zhimin
Abstract : Poly(β-L-malic acid) (PMLA) is a natural polyester produced by numerous microorganisms. Regarding its biosynthetic machinery, a nonribosomal peptide synthetase (NRPS) is proposed to direct polymerization of L-malic acid in vivo . Chemically versatile and biologically compatible, PMLA can be used as an ideal carrier for several molecules, including nucleotides, proteins, chemotherapeutic drugs, and imaging agents, and can deliver multimodal theranostics through biological barriers such as the blood–brain barrier. We focus on PMLA biosynthesis in microorganisms, summarize the physicochemical and physiochemical characteristics of PMLA as a naturally derived polymeric delivery platform at nanoscale, and highlight the attachment of functional groups to enhance cancer detection and treatment. Highlights: Genome-wide analyses have recently been used to map the genes encoding PMLA synthetase in different microorganisms. High-grade production of PMLA from fermentation by fungi or myxomycetes enables increasing applications of this biodegradable polymer in medical research. PMLA-based nanoconjugates can successfully penetrate the blood–brain barrier in rodent models, thus delivering imaging and/or therapeutic reagents to intrabrain targets and showing great potential for treating neurological disorders in human. With unmatched compatibility and resorbability, biosynthetic PMLAs are good examples of future macromolecular compounds generated by a green and sustainable approach, eventually benefiting human health.